1979
DOI: 10.1177/1077727x7900700502
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Clothing and Adjustment

Abstract: The major objectives of this research were to explore two basic general questions: (1) does race, sex, or grade influence clothing and social and personal adjustment variables, and (2) what are the relationships among clothing attitudes and adjustment variables? The subjects were 213 fe males and males (age range 14–19), Blacks and Whites, ninth and tenth grade, in a city high school. Demographic facts of race, sex, and grade were transcribed from school records. A question naire was designed in three sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Because previous studies of clothing deprivation have revealed inconsistent results for the variable sex (Cheek, 1978;Drake & Ford, 1979;Stuart, 1983;Vener & Hoffer, 1959), an analysis of variance was conducted to test the effect of sex on clothing deprivation for the current sample. Because previous studies of clothing deprivation have revealed inconsistent results for the variable sex (Cheek, 1978;Drake & Ford, 1979;Stuart, 1983;Vener & Hoffer, 1959), an analysis of variance was conducted to test the effect of sex on clothing deprivation for the current sample.…”
Section: Resultsmentioning
confidence: 99%
“…Because previous studies of clothing deprivation have revealed inconsistent results for the variable sex (Cheek, 1978;Drake & Ford, 1979;Stuart, 1983;Vener & Hoffer, 1959), an analysis of variance was conducted to test the effect of sex on clothing deprivation for the current sample. Because previous studies of clothing deprivation have revealed inconsistent results for the variable sex (Cheek, 1978;Drake & Ford, 1979;Stuart, 1983;Vener & Hoffer, 1959), an analysis of variance was conducted to test the effect of sex on clothing deprivation for the current sample.…”
Section: Resultsmentioning
confidence: 99%
“…Adolescents gain acceptance and security by consuming (and dressing) in ways considered to be acceptable by their peer groups. This is why Drake and Ford () argue that “permitting adolescents to dress like others, may aid in the development of self and move them toward greater self‐acceptance” (p. 290). This “group‐person connectivity” is often used by advertisers to encourage participation in adolescent‐directed campaigns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, considering that clothing (Darley, ) and sports trainers/sneakers (Hogg, Bruce, & Hill, ) are particularly socially and psychologically relevant to teenagers, it is not surprising that these item categories bear specific significance for them. After all, “anything that promises to gain acceptance for the adolescent receives considerable attention, particularly in the area of personal appearance” (Drake & Ford, , p. 283).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Psikolojik iyi oluşun yapı taşlarından biri olan kendini kabul etme (self-acceptance) (Ryff, 1989), ergenlik döneminde de tarih boyunca önemli bir yer tutmuştur (bkz., Drake ve Ford, 1979;Medinnus, 1965). Düşük SES'den ergenlerin varlıklı yaşıtlarını kendilerinden daha yetkin ve fiziksel olarak daha çekici görmeleri ergenlerin kendilerini kabul etmelerini zorlaştırıyor olabilir.…”
Section: Psikolojik İyi Oluş Alanyazınına Katkılarunclassified